Vol.2 - Benjamin, Joseph (ed.) (New Delhi, 2006)
The path breaking book Minorities in Indian social System is multi-layered comprehensive analysis characterized by profound scholarship of the perennial theme-place and role of minorities in Indian federal set up. Right from the momentous debates in Constituent Assembly with historical echoes going back to the British Raj till 2005-the intervening period of 58 years has witnessed legal, economic, political and cultural policies being so shaped that minorities of all hues and colors can live as equal and honorable citizens of the Indian Republic. No mean achievement by any long shot when one looks around the world.
Keywords: Minorities-India